Miners' lamp lapel pin, 1926 (1926)
1926 1918-1939 "Miners' lamp lapel pin, 1926" [T0493.jpg], 1926 These miniature copper-coloured miner's lamp pins or badges were sold by the Miners Federation of Great Britain at 1 shilling each to raise money for the Miners Wives and Childrens Relief Fund following the end of the 1926 General Strike.